Home » Simplify 3(frac{1}{3}) – 1(frac{1}{4}) x (frac{2}{3}) + 1(frac{2}{5})

Simplify 3(frac{1}{3}) – 1(frac{1}{4}) x (frac{2}{3}) + 1(frac{2}{5})

Simplify 3(frac{1}{3}) – 1(frac{1}{4}) x (frac{2}{3}) + 1(frac{2}{5})
  • A.
    2
  • B.
    3
  • C.
    4
  • D.
    5
Correct Answer: Option C
Explanation

3 – (frac{1}{3}) – ((frac{5}{4}) x (frac{2}{3})) + 1(frac{2}{5})
= (frac{10}{3}) – (frac{5}{6}) + (frac{7}{5})
= (frac{100 – 25 + 42}{30})
= (frac{117}{30})
= 3.9
(approx) 4

Related:  Show that (frac{sin 2x}{1 + cos x}) + (frac{sin2 x}{1 - cos x}) is